Failures Root Cause Analysis for Sewer Pipeline Network System - JAROOR, SAADI (2023)
Wastewater System is one of the most critical infrastructure systems. It is known that there are several types of Wastewater, and this dissertation is concerned with the Sewer type of Wastewater in particular. In addition, there are several systems of Sewer Wastewater as the dissertation is centered around Sewer Wastewater Pipeline Systems. Furthermore, there are two types of Sewer Wastewater Pipeline Systems: the gravity and pressure systems, and both systems will be discussed in this dissertation. The Sewer Wastewater Pipeline System was chosen for several reasons, the most important of which is finding Sewer Wastewater Pipeline System failures that affect the Sewer Wastewater as a whole System. In addition, to the danger effects of Sewer Wastewater Pipeline System failures. These effects may reach the residents of the area where the Sewer Wastewater Pipeline System failures occur. Furthermore, there are very harmful environmental effects. This dissertation aims to study the Sewer Pipelines system failures in an infrastructure organization in one of the Middle East countries. The period of data collected from 2014-2022. For studying and analyzing this topic, some techniques will be used Failure Rate, Pareto Chart, FMEA, and Fishbone Diagram. The research findings are summarized as the failure rate of the Gravity Pipeline system is higher than the Pressure Pipeline system. Also, the most frequent system failures are Pipeline broken, joint dislocation, connection broken, and damage. In addition, the most important consequences of the sewage pipeline system effects are the health, environmental impact, and road collapse in some failure cases. Furthermore, the most critical root cause is Third Party, Water Hammer, and Groundwater movement.